2011
DOI: 10.2298/tsci100629081c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electronic expansion valve on the performance of small window air conditioner retrofitted with R407C and R290

Abstract: The objective of this study is to investigate the influence of Electronic Expansion Valve (EEV) on the performance of window air conditioner retrofitted with R407C and R290. The window air conditioner applying the EEV is tested by varying the compressor inlet superheat from 0?C to 20?C. The eco friendly refrigerant R407C has the similar thermodynamic properties as those of R22 with an exception of temperature gliding during the phase change at constant pressure. R290 is a hydrocarbon which al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Chinnaraj et al [76] experimented with R407C and R290 in a 3.5 kW window air conditioner. It has been reported that the electronic expansion valve shows good overall performances comparing the capillary tube system.…”
Section: Based On Changes In Components Of the Systemmentioning
confidence: 99%
“…Chinnaraj et al [76] experimented with R407C and R290 in a 3.5 kW window air conditioner. It has been reported that the electronic expansion valve shows good overall performances comparing the capillary tube system.…”
Section: Based On Changes In Components Of the Systemmentioning
confidence: 99%
“…In order to increase the efficiency of the air conditioning system, several concepts have been studied, such as free cooling 17,18 and free cooling coupled with heat storage systems; 19 night ventilation; 20 using evaporative cooling; 2123 coupling the buildings with earth heat exchangers; 22,24,25 employing chillers with: two compressors, 26 variable-speed compressor, 27 electronic expansion valve, 27,28 variable refrigerant flow systems, 24,29,30 or with new refrigerants; 31 using absorption or adsorption chillers, either driven by solar energy 3234 or waste heat; 35,36 replacement of dry cooling towers by evaporative cooling towers; 37–39 improvement of control systems; 40–44 improvement of chiller condensation using swimming pools as heat links, 45 or even using aquifers as thermal storage. 46 In a recent review work, 47 different aspects that contribute to the energy efficiency on air conditioning systems were analyzed: novel cooling devices, innovative system designs and integration, and operational management and control.…”
Section: Introductionmentioning
confidence: 99%